Multicultural Education to Develop Tolerance of Santri - Umar, M. Abdullah; Nurrohman, Wahyu (Multicultural Islamic Education Review, 2024)
Pondok Pesantren is one of the faith-based educational institutions where students of various ethnicities, religions, races, and cultures. with the diversity of tribes, races, and cultures they bring different cultures and cultures to then be able to coexist and adapt to the community (students, administrators, caregivers) of other cottages. In addition, some students come from different backgrounds. The purpose of research in this study is to examine multicultural education to develop students' tolerance attitudes. The results showed that multicultural education in the tradition of pesantren education develops the tolerance attitude of students by providing tolerance education, moral education, moral education, and family education through various methods or means, such as supervisory advice, providing punishment for violators, and example. In addition, the Islamic Boarding School provides several programs to foster students, including providing regulations to students such as curfew restrictions, language zones, placement of multicultural student dormitories, directing students to maintain a way of speaking to anyone, creating student culture at the end of each semester, giving punishment to students who violate.